Measuring Attitudes toward Open Adoption: Spanish Validation of the Open Adoption Scale - Ana Berástegui; Jesús Oliver; Susana Corral; Carles Perez-Testor; Irene Calvo; Judith Lorente-De-Sanz; Mireia Sanz; Scott D. Ryan (Anuario de Psicología Jurídica)

(untitled)
Background: Open adoption is a kind of adoption in which some degree of communication is formalized between the biological family and the adopted child or adoptive family. The present study analyzes the psychometric properties of the Spanish adaptation of the Open Adoption Scale, an instrument that assesses various negative attitudes toward open adoption. Method: The study involved 440 participants of both sexes who completed a sociodemographic questionnaire and the Open Adoption Scale. An exploratory factor analysis was performed with half of the sample and a confirmatory factor analysis with the other half. Results: High internal consistency indices were observed. Furthermore, an exploratory factor analysis and a confirmatory factor analysis supported construct validity. Finally, the strong relationships observed between the scale and four myths about the absence of benefits of open adoption supported convergent validity. Conclusions: The results support using the Spanish version to assess attitudes toward open adoption. Assessing attitudes toward open adoption is essential to implementing it, selecting candidates, and evaluating training processes for technicians and families.